2021
DOI: 10.1371/journal.pone.0257639
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of a community-based exercise intervention on cardiorespiratory fitness, cardiovascular health, strength, flexibility and physical activity among adults living with HIV: A three-phased intervention study

Abstract: Purpose Our aim was to examine the impact of a community-based exercise (CBE) intervention on cardiorespiratory fitness, cardiovascular health, strength, flexibility, and physical activity outcomes among adults living with HIV. Methods We conducted a longitudinal intervention study with community-dwelling adults living with HIV in Toronto, Canada. We measured cardiopulmonary fitness (V̇O2peak (primary outcome), heart rate, blood pressure), strength (grip strength, vertical jump, back extension, push-ups, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 74 publications
3
21
0
1
Order By: Relevance
“…Findings from this study revealed significant improvement in the cardiorespiratory fitness/aerobic capacity (VO2max) within the intervention group, and between the groups after 8-week exercise intervention. This result is in tandem with the report of O'Brien et al [16] , that a community-based exercise intervention had a significant effect on V ̇O2peak (0.56 ml/kg/min; 95% CI: -1.27, 2.39). The result is in agreement with findings of Ibeneme et al [17] that carried out a systematic review with meta-analysis which reported a significant improvement in VO2 max following exercise intervention in people living with HIV.…”
Section: Discussionsupporting
confidence: 88%
“…Findings from this study revealed significant improvement in the cardiorespiratory fitness/aerobic capacity (VO2max) within the intervention group, and between the groups after 8-week exercise intervention. This result is in tandem with the report of O'Brien et al [16] , that a community-based exercise intervention had a significant effect on V ̇O2peak (0.56 ml/kg/min; 95% CI: -1.27, 2.39). The result is in agreement with findings of Ibeneme et al [17] that carried out a systematic review with meta-analysis which reported a significant improvement in VO2 max following exercise intervention in people living with HIV.…”
Section: Discussionsupporting
confidence: 88%
“…The reduction in systolic blood pressure is consistent with previous literature showcasing that any PA can reduce blood pressure and reduce/prevent hypertension risk among adults 69 and PWH. 70,71 Even though the average blood pressure of the participants in the study was in the "elevated" range (according to the American College of Cardiology/American Heart Association [ACC/AHA] Guidelines), 72 our data align with the current literature suggesting that even among OPWH, engaging in PA can show improvements in cardiovascular outcomes. 68,[73][74][75][76] The findings of the present study are subject to certain limitations.…”
Section: Discussionsupporting
confidence: 66%
“…CBE can cultivate social interaction, encourage regular exercise and facilitate self-management strategies in PLWH to independently manage health challenges 26–29. Additionally, CBE can provide physical health benefits in PLWH such as a decrease in lipid profile, waist circumference, diastolic and systolic blood pressure, and an increase in upper and lower body muscular strength 28 30 31. Despite the benefits of CBE, PLWH may experience barriers to exercising in traditional gym environments, including, interpersonal, financial and geographical barriers, self-image issues and stigma, and difficulty initiating exercise following periods of inactivity 26 29.…”
Section: Introductionmentioning
confidence: 99%